2021
DOI: 10.1101/2021.12.03.471139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human brain networks mediating the vestibular sensation of self-motion

Abstract: Activation of the peripheral vestibular apparatus simultaneously elicits a reflex vestibular nystagmus and the vestibular perception of self-motion (vestibular-motion perception) or vertigo. In a newly characterised condition called Vestibular Agnosia found in conditions with disrupted brain network connectivity, e.g. traumatic brain injury (TBI) or neurodegeneration (Parkinson's Disease), the link between vestibular reflex and perception is uncoupled, such that, peripheral vestibular activation elicits a vest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, the larger gains and phase leads of the irregular afferents are required to drive robust postural responses since vestibulo-spinal pathways must account for the higher inertia of the body relative to the eye [ 27 , 42 ]. Furthermore, irregular afferents likely also make important contributions to ascending pathways that convey vestibular information to cortical brain circuits mediating self-motion perception ([ 43 ]; also reviewed in [ 14 ]). Interestingly, a recent imaging study in humans reported that these cortical circuits overlap with those mediating postural control [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the larger gains and phase leads of the irregular afferents are required to drive robust postural responses since vestibulo-spinal pathways must account for the higher inertia of the body relative to the eye [ 27 , 42 ]. Furthermore, irregular afferents likely also make important contributions to ascending pathways that convey vestibular information to cortical brain circuits mediating self-motion perception ([ 43 ]; also reviewed in [ 14 ]). Interestingly, a recent imaging study in humans reported that these cortical circuits overlap with those mediating postural control [ 44 ].…”
Section: Discussionmentioning
confidence: 99%